The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0278364917693927
|View full text |Cite
|
Sign up to set email alerts
|

Phase estimation for fast action recognition and trajectory generation in human–robot collaboration

Abstract: This paper proposes a method to achieve fast and fluid human–robot interaction by estimating the progress of the movement of the human. The method allows the progress, also referred to as the phase of the movement, to be estimated even when observations of the human are partial and occluded; a problem typically found when using motion capture systems in cluttered environments. By leveraging on the framework of Interaction Probabilistic Movement Primitives, phase estimation makes it possible to classify the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 32 publications
0
64
0
Order By: Relevance
“…Levine et al [123] demonstrated the high potential of deep learning algorithms for automated flexible robotic grasping of different objects in undefined poses. Maeda et al [144] proposed a method to achieve fast and fluid human-robot interaction by estimating the progress of the movement of the human. Their method (Fig.…”
Section: Programming-free Robot Controlmentioning
confidence: 99%
“…Levine et al [123] demonstrated the high potential of deep learning algorithms for automated flexible robotic grasping of different objects in undefined poses. Maeda et al [144] proposed a method to achieve fast and fluid human-robot interaction by estimating the progress of the movement of the human. Their method (Fig.…”
Section: Programming-free Robot Controlmentioning
confidence: 99%
“…In Maeda et al original work [5], each demonstration (which used static observation windows (SOW))was resampled yielding a nominal duration T nom_sow . We adjust the definition of the nominal duration to fit the length of the dynamic observation window (DOW) duration yielding T nom_dow .…”
Section: Phase Estimation With Dynamic Observation Windowsmentioning
confidence: 99%
“…To determine the best phase estimate during test time, we use the single phase temporal model in [5]. A distribution of phase ratios across demonstrations is modeled as a normal distribution and set as the phase prior: α dow ∼ N (µ α dow , σ α dow ).…”
Section: Phase Estimation With Dynamic Observation Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our work, each demonstration was resampled yielding a nominal duration T norm . As in [8], we assume that the i th demonstration also has a constant temporal change in relation to the nominal duration and can define a scaling factor in Eqtn. 11 to index all demonstrations by the nominal time index.…”
Section: Phase Estimationmentioning
confidence: 99%